Shelley Seaton in conversation with Jerome Carson. Issue 1 (18th January 2019) - Seaton, Shelley; Carson, Jerome
Abstract : Purpose: The purpose of this paper is to provide a profile of Shelley Seaton. Design/methodology/approach: Shelley gives a short background to her life story and is then interviewed by Jerome. Findings: Shelley tells us about a number of life events that impacted on her mental health issues, starting with childhood bullying and also abusive relationships. Research limitations/implications: The case study approach privileges the person's lived experience. It also lets us see the unique complexity of each person's story. Practical implications: Shelley received little help in the form of counselling either at school or when she experienced post-natal depression. Social implications: When mental health problems start in childhood, schools have a vital role to play. While the bullying stopped when Shelley's Mum went to the school, the damage was already done. She was given no support to help her through this. Originality/value: Patricia Deegan has asked, "Could you have survived what this person has survived?" (Deegan, 1996, p. 95). Shelley's story is a tale of survival.